Bi2O2S nanosheets anchored on reduced graphene oxides as superior anodes for aqueous rechargeable alkaline batteries. (20th September 2022) - Liu, Yi-Lin; Li, Meng-Qiu; Wang, Gui-Gen; Dang, Le-Yang; Li, Fei; Yan, Dong; Tan, Man-Lin; Zhang, Hua-Yu; Yang, Hui Ying
Abstract: To achieve high-performance aqueous rechargeable alkaline batteries (ARABs), durable and high-rate anode materials should be developed. Bi-based materials have always been considered as promising anodes due to their enormous capacity, adequate negative operating voltage range, and three-electron redox characteristics. Nonetheless, the poor kinetics and low cycling stability of bi-based materials have severely limited their applications for ARABs. Here inspired by the unique structural characteristic of two-dimensional (2D) materials with a fast ion diffusion channel and relatively robust structure, 2D/2D Bi2 O2 S@rGO nanosheets were synthesized using a one-step hydrothermal process as the anode material for ARABs. At a current density of 1 A g −1, the as-optimized anodes exhibit a high specific capacity of 250.51 mAh g −1 . Using Bi2 O2 S@rGO NSs as the anode and (NiCo)9 S8 as the cathode, the full cell exhibit a high energy density of 82.91 W h kg −1, a high power density of 7.59 kW kg −1, and excellent cycling stability, with a capacity retention rate of 92.74% after 5, 000 cycles. This work could open up a way for environmentally friendly and high-performance anode materials.